2017
DOI: 10.1002/jbt.22005
|View full text |Cite
|
Sign up to set email alerts
|

Potential cow milk xanthine oxidase inhibitory and antioxidant activity of selected phenolic acid derivatives

Abstract: Xanthine oxidase (XO) found in all mammals and excess activity leads to urolithiasis. The cow milk XO was purified to 305-fold with a specific activity of 8.76 EU/mg and overall yield of 87% by using DEAE-Sepharose chromatography. The phenolics showed potent XO inhibitory effect with K i , P1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
1
8
0
2
Order By: Relevance
“…Cos et al (1998) 2 scavenging nor XOD inhibition activity, or type VIadditional pro-oxidant activity but no XOD inhibition. Similar results were also observed by Nile et al (2018), who reported that phenolic acids potently inhibit the XOD enzyme and possess a strong antioxidant activity. Similar results were also observed by Nile et al (2018), who reported that phenolic acids potently inhibit the XOD enzyme and possess a strong antioxidant activity.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Cos et al (1998) 2 scavenging nor XOD inhibition activity, or type VIadditional pro-oxidant activity but no XOD inhibition. Similar results were also observed by Nile et al (2018), who reported that phenolic acids potently inhibit the XOD enzyme and possess a strong antioxidant activity. Similar results were also observed by Nile et al (2018), who reported that phenolic acids potently inhibit the XOD enzyme and possess a strong antioxidant activity.…”
Section: Discussionsupporting
confidence: 88%
“…Previously, various authors reported that hydroxycinnamic acid, flavonoids, and other bioactive compounds potently inhibit the XOD enzyme (Nile et al, 2018;Nguyen et al, 2006;Pathak, Gupta, Shukla, & Baunthiyal, 2018;Qu et al, 2017;Zhang et al, 2016). The A similar inhibitory mode has been observed in various bioactive compounds Gawlik-Dziki et al, 2017;Lin et al, 2015;Pathak et al, 2018;Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations